Contabilidad medioambiental en España: proceso estructurado de revisión y análisis teórico referencial - Silva da Rosa, Fabricia (2012)
One way to perceive and understand the level of development of environmental accounting is to study the main features of its publications. Thus, the purpose of this paper is to identify and analyze the profile of Spanish publications in accounting journals. To this end, 15 journals were selected and analyzed 74 articles in the period 2001 to 2010. The results show that the peak years of publication are 2001, 2003 and 2006, and authors with more articles in the sample are Moneva Abadía, Larrinaga González, Fernández Cuesta and Archel Domench. In terms of methodology, the works of review, case studies and content analysis, addressing standardization issues, fundamentals of environmental accounting, environmental sustainability indicators and reporting.